Peningkatan Pengetahuan Melalui Edukasi Dan Implementasi Health Jus Mesem Sebagai Alternatif Terapi Hipertensi - Gumi, Iga Defitri Fefita; Liza, Monika; Handini, Bella Rahma; Sari, Rica Meiriska; Melinda, Anggun Dwi; Sari, Fikitri Marya (Universitas Dehasen Bengkulu, 2026)
Hypertension is a non-communicable disease that carries the risk of serious complications, including heart disease, stroke, and kidney failure. In Kepahiang Regency, the prevalence of hypertension is high, yet most sufferers do not receive optimal health care. A community service activity was conducted through lectures and demonstrations on making MESEM juice (cucumber, celery, lemon, and honey) in Hamlet 3, Sumber Sari Village, with 25 participants, mostly elderly and women. The training covered the definition, symptoms, causes, and prevention of hypertension, as well as how to make MESEM juice as a non-pharmacological therapy. Results showed that the lecture and presentation methods effectively increased participants' knowledge, awareness, and ability to use MESEM juice as a supportive therapy for hypertension. This approach encourages the adoption of healthy lifestyles, blood pressure control, and reduced risk of complications, serving as a model for integrated interventions combining health education, natural therapies, and medical treatment in rural communities.